Rising Wage Inequality in Mexico, 1984-2000: A Distributional Analysis - Popli, Gurleen K. (Journal of Income Distribution®, 2007)
In this study we look at distribution of wages to examine the extent and cause ofthe increasing wage inequality in Mexico over the two decades encompassing 1984and 2000. To understand the causes of the increase in inequality over time we doa counterfactual analysis. We find that over the last two decades not only did theinequality increase, there also was an erosion of real wages, and it is the middle classwhich was affected the most. The main reason for the decrease in real wages wasdeclining unionization in the country, while the main reason for the rise in inequalitywas changing distribution of skills.